CERTAINTY OF LAW FOR NOTARY CANDIDATES IN REGIONS THAT ESTABLISH THE LARGE-SCALE SOCIAL RESTRICTIONS IN EAST JAKARTA CITY - Agung, Muhammad Maghfur; Sukarmi, Sukarmi; Sjafiie, RR. Imam Rachmad (Nurani, 2021)
The purpose of this article is discussing the law problem that has relations to certainty of law for notary candidates in regions that establish large-scale social restrictions. WHO establish the COVID-19 as the Public Health Emergency of International Concern (PHEIC). The spread controlling of Covid-19, the Indonesian government apply several strategies, the one of strategy is Establish large-scale social restrictions. Large-scale social restrictions cause closed the office. Notary candidates apprentice become closed or get free days. The problem is counting the 24 months apprentice of notary candidates if the regions apply the large-scale social restrictions until the office of notary candidates closed for a while. This research is an empiric juridical. The result of this research that use the method above, researcher obtains the answer of the problem that certainty of law for notary candidates in the regions that apply the large-scale social restrictions based on law regulation.